Short Communication: Biodiversity of weeds in Ilmen State Reserve, Russia - IRINA V. MASHKOVA; TATYANA G. KRUPNOVA; ANASTASIYA M. KOSTRYUKOVA; NIKITA E. VLASOV (Society for Indonesian Biodiversity, 2018)
Mashkova IV, Krupnova TG, Kostryukova AM, Vlasov NE. 2018. Short Communication: Biodiversity of weeds in Ilmen State Reserve, Russia. Biodiversitas 19: 106-111. Weeds are a synanthropic flora. Human exposure to the natural landscape leads to the spread of synanthropic plant species, so weeds begin to occupy a significant place in the structure of ecosystem biodiversity. The aim of this study was to investigate the weeds biodiversity structure and to assess the extent of invasion of weeds into the territory of the Ilmen State Reserve in South Urals, Russia. This paper presents the results of study of weeds during the vegetation period in 2013–2017. Fifty one species of weeds distributed in four genera and six families were found on the territory of the Southern Forestry of the Ilmen State Reserve. Besides, the differences between species diversity of weeds on three types of roads (gravel, earth and foot) and on two types of forests (birch and pine) were also discovered in this study . The greatest degree of invasion was discovered for foot roads. It was noted that pine forest is the most resistant the invasion of weeds.